Impact of Signal Peptides on Furin‐2A Mediated Monoclonal Antibody Secretion in CHO Cells. Issue 9 (14th August 2017) - Lin, Jian'er; Neo, Shu Hui; Ho, Steven C. L.; Yeo, Jessna H. M.; Wang, Tianhua; Zhang, Wei; Bi, Xuezhi; Chao, Sheng‐Hao; Yang, Yuansheng
Abstract : Studies had shown the benefits of using furin‐2A peptides for high monoclonal antibody (mAb) expression in mammalian cells. How signal peptides affect furin‐2A mediated mAb secretion has yet to be investigated. The impact of signal peptides on mAb secretion in furin‐2A based tricistronic vectors in CHO cells is evaluated. In each tricistronic vector, heavy chain (HC) is arranged as the first cistron and followed by a furin recognition sequence, a 2A peptide, light chain (LC), an internal ribosome entry site (IRES), and dihydrofolate reductase (DHFR). Signal peptides for HC and LC are either removed or changed in different vectors. The vectors with signal peptides on both HC and LC genes gIve the highest mAb secretion levels. Changing to signal peptides with different strengths on either HC or LC do not change the mAb secretion level. IgG is still secreted when the signal peptide on the LC gene is removed but at a lower level compared to the vectors containing signal peptides on both HC and LC genes. Removing the HC signal peptide results in almost no IgG secretion regardless of whether the downstream LC carries any signal peptide. Removing the furin cleavage site does not affect mAb secretion levels while removing the 2A sequence results in low mAb secretion. The results present here will be beneficial for designing furin‐2A based vectors for expressing mAb in mammalian cells. Abstract : There are conflicting reports regarding whether a signal peptide is necessary for the protein downstream of 2A to enter into the ER for secretion when the protein upstream of 2A bears a signal peptide. In this study, it is demonstrated that heavy chain and light chain peptides expressed from 2A cannot enter ER and form IgG without the help of signal peptides. When the heavy chain gene upstream of 2A bears a signal peptide, IgG is able to be secreted even if the signal peptide on the light chain (LC) gene is removed but at a lower level compared to the vectors containing signal peptides on both heavy chain and light chain genes. These results will be beneficial for designing 2A‐based vectors for expressing monoclonal antibodies and other recombinant proteins in mammalian cells.